JOB DEMANDS – JOB RESOURCE: SYSTEMATIC LYTERATURE REVIEW - Aris Prilatama; Cindy Pramita; Sopiah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This systematic literature review aims to summarize various studies on the relationship between job demands and job resources. This research utilized the SLR (Systematic Literature Review) method. Journals were obtained from Publish or Perish by selecting Scopus sources. The keywords used were "job demands" and "job resources" and after conducting the search from Publish or Perish, a total of 200 records were filtered within the years 2018-2023. Subsequently, these records were verified, resulting in 30 articles that met the criteria. The results indicate that job demands can deplete physical, psychological, and cognitive resources, which can have negative consequences for employees. In contrast, job resources can fulfill basic psychological needs, increase employee engagement, and foster creativity.